Fast Self‐Assembly of Photonic Crystal Hydrogel for Wearable Strain and Temperature Sensor. Issue 7 (6th May 2022) - Liu, Haiyang; Wang, Yan; Shi, Zhekun; Tan, Di; Yang, Xichen; Xiong, Lingheng; Li, Gang; Lei, Yifeng; Xue, Longjian
Abstract: Structural colors from photonic crystals (PCs) have attracted emerging attention in the research area of wearable sensors. Conventional self‐assembly of PC takes days to weeks. Here, a fast self‐assembly method of PC with horizontal precipitation of silica nanoparticles (NPs) in a polydimethylsiloxane fence, which can be completed within 1–4 h depending on the fence parameters, is introduced. The resultant PC exhibits tunable structural colors in the entire visible spectrum. With infiltration of composite hydrogels containing acrylic acid, acrylamide, chitosan, and carbon nanotubes (CNTs) into the gaps of NPs to form an inverse opal PC, a structural color hydrogel that can quickly respond to different stimuli, including strain and temperature, is obtained. Moreover, with the addition of CNTs, the composite PC hydrogel can also output an electronic signal together with optical color changes. Based on these extraordinary responsive behaviors, the PC hydrogel sensor for quantitative feedback to external stimuli of stretching, bending, pressing, and thermal stimuli, with brilliant color change and electronic signal outputs simultaneously, is demonstrated. This fast‐assembled PC hydrogel with excellent responsive properties has great potential for applications in wearable devices, mechanical sensors, temperature sensors, and colorimetric displays. Abstract : A fast self‐assembly method of photonic crystal (PC) is developed with horizontal precipitation of silica nanoparticles in polydimethylsiloxane fence, which can be completed within 1–4 h. The wearable device with PC hydrogel can serve as strain sensor and temperature sensor, with brilliant color changes and electronic signal outputs simultaneously.